Physiological concepts of high intensity interval training improving aerobic capacity: a systematic review - Cahyanto Wibawa, Junian (Bravo's: Jurnal Program Studi Pendidikan Jasmani dan Kesehatan, 2025)
Enhancing athletes' physical capabilities is necessary to promote success. There is a strong correlation between a healthy body and the training performance that results. High-intensity exercise and recovery time are combined in the sport known as high intensity interval training (HIIT). The purpose of HIIT training is to improve an athlete's strength, speed, and physical stamina. Objective. This study sought to determine the effects of high-intensity interval training (HIIT) on athletes' VO2max. Additionally, this study offers a theoretical foundation for using HIIT training to enhance athletes' physical performance. Materials and methods. We looked through a number of literature databases for our systematic review study, including Pubmed, Web of Science, and Science Direct. Articles over the past five years that address athletes, HIIT training, and VO2max. Using the Web of Science, Pubmed, and Science Direct databases, 437 papers published in the last five years were located. For this systematic review, ten papers that satisfied the inclusion criteria were chosen and reviewed. Standard operating procedures were evaluated in this study using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA). Results. A systematic review has demonstrated that HIIT exercise increases athletes' aerobic capacity. HIIT training has been shown to significantly enhance athletes' physical condition. Conclusions. It has been demonstrated that HIIT training greatly raises athletes' aerobic capacity by raising their VO2max.  In order to complement athletes' accomplishments, it is suggested that this be used as a training menu